A facile synthesis of γ-butenolides via cyclization of 3-alkenoic acids with dimethyl sulfoxide and oxalyl bromide. Issue 21 (2nd November 2019) - Ding, Rui; Liu, Yongguo; Liu, Lei; Li, Huimin; Tao, Sichen; Sun, Baoguo; Tian, Hongyu
Abstract: The combination of dimethyl sulfoxide and oxalyl bromide was used to accomplish the cyclization of 3-alkenoic acids with the aid of a base to afford γ-butenolides, in which bromodimethylsulfonium salt generated in situ was proposed to serve as a Br + source. GRAPHICAL ABSTRACT: